2012
DOI: 10.4161/cc.20309
|View full text |Cite
|
Sign up to set email alerts
|

ZFP36 expression impairs glioblastoma cell lines viability and invasiveness by targeting multiple signal transduction pathways

Abstract: (2012) ZFP36 expression impairs glioblastoma cell lines viability and invasiveness by targeting multiple signal transduction pathways, Cell

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
24
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(26 citation statements)
references
References 43 publications
2
24
0
Order By: Relevance
“…4D) of U87MG cells. Consistent with these findings, expression of TTP has been shown to suppress cell growth and invasion in brain and colon cancer cells (Selmi et al, 2012;Stoecklin et al, 2003). These findings indicate that TTP performs a tumor suppressor function by regulating the mRNA stability of ARE-containing genes such as uPA and uPAR.…”
Section: Discussionsupporting
confidence: 72%
“…4D) of U87MG cells. Consistent with these findings, expression of TTP has been shown to suppress cell growth and invasion in brain and colon cancer cells (Selmi et al, 2012;Stoecklin et al, 2003). These findings indicate that TTP performs a tumor suppressor function by regulating the mRNA stability of ARE-containing genes such as uPA and uPAR.…”
Section: Discussionsupporting
confidence: 72%
“…Previous studies reported that TTP regulated the mRNA decay of PIM1 and PIM3 but not that of PIM2 (Kim et al ., ; Mahat et al ., ; Selmi et al ., ). Our study showed a negative feedback loop between PIM family proteins and TTP through the PIM2‐degradation of TTP.…”
Section: Discussionmentioning
confidence: 97%
“…Even though the immunophenotype is similar for LSC derived from different cells of origin, there are reproducible differences in gene expression. For example, Evi1, c-jun, Fos1, Bcl6 (Parekh et al, 2008), Gsr1, Nedd9 and Zfp36 (Selmi et al, 2012) are highly expressed in HSC-derived LSC but not GMP derived LSC (Supplemental Figure 6F). Therefore we demonstrate that the cell in which the oncogene is initially expressed can influence the final gene expression program of the LSC even if the LSC represents a stage of hematopoietic development further downstream of the HSC.…”
Section: Discussionmentioning
confidence: 99%